Leituras da tradição em Macunaíma, de Mário de Andrade, e Adán Buenosayres, de Leopoldo Marechal - Joana Alves Fhiladelfio (2016)
Starting from the articulation of socio-cultural aspects with the literary text, this work consists of a comparative analysis of literary works, Macunaíma, written by the Brazilian Mário de Andrade, and Adán Buenosayres, written by the Argentine Leopoldo Marechal. Our goal is to draw a parallel between the textual and intertextual procedures used by the authors, by checking which readings they do from tradition, since both are built as a mosaic of a multitude of pre-existing texts, different in nature, coming both from the oral tradition and as well as the writing, popular, classical, national and universal tradition. As methodological procedure, we adopt the perspective of literary comparatism, since in the analysis of the works, it is necessary to establish clashes between them, between the authors, between production environments and their approaches and departures to other works since, in the analysis of the works, it is necessary to establish clashes between them, between the authors, between the production environments and their approaches and clearances to other works. We hope this thesis, in addition to expanding knowledge about these two writers, texts and their contexts, can provide a desirable dialogue and mutual knowledge of literature, culture and history of these two countries.